Understanding The Concept of Plant Diversity by Utilising The School Environment In Biology Lessons - Ahmad Amin; Hetdy Sitio; Justin Farrell; Abather Rahi Saadoon; Michael Robin Pangihutan Simanjuntak (PT. TAROMBO RESEARCH DEVELOPMENT pak, 2026)
The result of preliminary observation at some SLTPN 10 Denpasar Municipality, showed that there were some difficulties faced by the teacher in the learning process. One of them was that it was difficult to teach concept understanding of plant diversity to the students. The purposes of this action research were (1) to fine out whether or not the benefit of school environment could improve the concept understanding of plant diversity, (2) to improve the student's ability in completing the group task in studying the plant diversity. The data were obtained from the test and observation, they were analyzed by the use of percentage. The result of data analysis showed the learning success in cycle I, 71,79%, in cycle II, 84,62%, and in cycle III, 94,87%. The showed that there was good improvement from cycle I, to cycle III. There fore the benefit of school environment could improve the student's concept understanding of plant diversity. The student's cooperation in completing the group task improve, seen from their activities in group discussion and their ability in completing the